Pengembangan Perangkat Lunak Simulasi Berbasis Virtual Reality untuk Pelatihan Medis dan Pembelajaran Interaktif - I Gede Partha Sindu; I Wayan Sukadana; Agus Adiarta; Dewa Ayu Putu Adhiya Garini Putri (Jurnal Profesi Insinyur Universitas Lampung, 2026)
The rapid advancement of Virtual Reality (VR) technology has created significant opportunities to enhance learning and training effectiveness in healthcare and educational settings. This study aims to develop a VR-based simulation software system for medical training and interactive learning that provides an immersive, interactive, and safe learning experience. The system was developed using the Agile software development approach, consisting of requirements analysis, system and user interface design, VR module development, VR hardware integration, and system testing and evaluation. The application was implemented using Unity 3D as the game engine, Blender for 3D modeling, and Meta Quest as the VR platform. System evaluation was conducted through functional testing, VR device compatibility testing, User Acceptance Testing (UAT), and user experience assessment using the User Experience Questionnaire (UEQ). The results demonstrate that the developed system operated successfully and achieved a user acceptance score of 88.16%, which falls within the “Very Good” category. Furthermore, the UEQ results indicated positive evaluations across all user experience dimensions, including attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. These findings suggest that VR technology has strong potential as an effective and innovative medium for medical training and interactive learning while supporting the digital transformation of healthcare education. The developed system provides a practical foundation for integrating immersive technologies into educational and clinical training environments.